The Association Between Generalized Trust and Physical and Psychological Health Across Societies - Hamamura, Takeshi; Li, L.; Chan, D. (Springer Netherlands, 2016)
Prior research found that physical and psychological health are positively associated with generalized trust of others. This association is known to vary across societies, though the extent of this variation and its source remains poorly understood. The current research examined whether differences in development across societies describe why the effects of trust on health differ across societies. Drawing on the dataset from the World Values Survey, we found that the participants’ generalized trust was associated with their physical health, happiness, and life satisfaction. Multi-level analysis showed that these associations varied substantially across societies. For physical health and happiness, the variation was related to differences in societal development. Generalized trust was more strongly associated with physical health and happiness in developed societies than in developing societies. © 2016 Springer Science+Business Media.